Use of antibiotics in upper respiratory infections on patients under 16 years old in private ambulatory medicine Uso de antibióticos en infecciones de vías respiratorias altas de niños atendidos en consulta externa privada - Ingris Peláez-Ballestas; Adolfo Hernández-Garduño; José Luis Arredondo-García; Jose Luis Viramontes-Madrid; Artemisa Aguilar-Chiu (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To assess antibiotic use for upper respiratory infections (URI) treatment on patients under 16 years-old who are beneficiaries of a pre-paid health care scheme. MATERIAL AND METHODS: A database containing the record of all the medical prescriptions for URI treatment, from May 1997 to April 1998 was analyzed. Patients were under 16 years old and had been diagnosed with common colds, pharyngitis, bronchitis, sinusitis, otitis, and other unspecified upper respiratory tract infections. Three hundred and fifty-one physicians of seven different specialties who attended 25 300 beneficiaries wrote such prescriptions. RESULTS: A total of 30 889 assorted medications were prescribed to 5 533 patients with the above diagnoses. Antibiotics were prescribed for 77.5% of all diagnoses, ranging from 58% for pharyngitis to 91% for laryngitis. The most frequently used antibiotics were: penicillin, cephalosporins, and macrolides. CONCLUSIONS: This study presents the information of antibiotics prescription practices for URI in a pre-paid health plan in Mexico. These findings may be used to support specific campaigns for rational use of antibiotics among children attended at private ambulatory health care practices. OBJETIVO: Evaluar el uso de antibióticos para tratar las infecciones de vías respiratorias altas (IVRA) en pacientes menores de 16 años con derecho a un sistema médico prepagado privado. MATERIAL Y MÉTODOS: De mayo de 1997 a abril de 1998 se analizó una base de datos de todas las recetas médicas para tratamiento de IVRA. Los pacientes eran menores de edad con diagnósticos de resfriado común, faringitis, bronquitis, sinusitis, otitis o de otras IVRA no especificadas. Las recetas fueron hechas por 351 médicos de siete especialidades, que atendieron a 25 300 beneficiarios. RESULTADOS: Fueron prescritos 30 889 tipos de medicamentos a 5 533 pacientes con los diagnósticos mencionados. Se recetaron antibióticos para 77.5% de todos los diagnósticos, desde 58% para faringitis hasta 91% para laringitis. Los antibióticos recetados más frecuentemente fueron: penicilina, cefalosporinas, y macrólidos. CONCLUSIONES: Este estudio presenta la información sobre las prácticas prescriptivas médicas para IVRA en una institución de atención médica privada en México. Los hallazgos de este estudio pueden ser utilizados para apoyar campañas específicas a favor del uso racional de antibióticos en niños atendidos en los sistemas privados de consulta externa.